Austrian Ideas for a United Europe (1789–2004) - Ziegerhofer, Anita (The Development of European and Regional Integration Theories in Central European Countries, 2022)
For centuries, a unified Europe has been a place of longing for many intellectuals. This is evidenced by the manifold conceptualizations of Europe that have been proposed since the 14th century. The search for ideas about Europe in the given period that originate from Austria first leads to federalist ideas of (Mittel-) Europe from the Habsburg Monarchy, which represent a ‘Europe en miniature.’ Only toward the end of the 19th century did Bertha von Suttner call for the foundation of a European Confederation. Beginning during the First World War and then manifesting in the interwar period, metropolitan Vienna served as a starting point and laboratory for implementing the European vision. Thus, the founder of the Pan-European Union, Richard Nikolaus Coudenhove-Kalergi, was the first visionary of Europe who tried to turn this idea into reality. With the process of European integration starting after the Second World War, the idea of unifying European states materialized, and visions for Europe that originated from Austria became rare. KEYWORDS: Federation plans – Habsburg Empire, Mitteleuropa, Pan-European Union, Kulturbund, European Union